Decontamination of coal mine effluent generated at the Rajrappa coal mine using phytoremediation technology. Issue 6 (3rd June 2017) - Lakra, Kalpana C.; Lal, B.; Banerjee, T. K.
ABSTRACT: Toxicity of the effluent generated at the Rajrappa coal mine complex under the Central Coalfields Limited (CCL, a subsidiary of Coal India Limited) in Jharkhand, India was investigated. The concentrations (mg L −1 ) of all the toxic metals (Fe, Mn, Ni, Zn, Cu, Pb, Cr, and Cd) in the coal mine effluent were above the safe limit suggested by the Environmental Protection Agency (EPA 2003). Among these, Fe showed the highest concentration (18.21 ± 3.865), while Cr had the lowest effluent concentration (0.15 ± 0.014). Efforts were also made to detoxify the effluent using two species of aquatic macrophytes namely "' Salvinia molesta and Pistia stratiotes." After 10 days of phytoremediation, S. molesta removed Pb (96.96%) > Ni (97.01%) > Cu (96.77%) > Zn (96.38%) > Mn (96.22%) > Fe (94.12%) > Cr (92.85%) > Cd (80.99%), and P. stratiotes removed Pb (96.21%) > Fe (94.34%) > Ni (92.53%) > Mn (85.24%) > Zn (79.51%) > Cr (78.57%) > Cu (74.19%) > Cd (72.72%). The impact of coal mine exposure on chlorophyll content showed a significant decrease of 42.49% and 24.54% from control values in S. molesta and P. stratiotes, respectively, perhaps due to the damage inflicted by the toxic metals, leading to the decay of plant tissues.